The Relationship Between mSOFA and the Ratio of Treatment Costs to BPJS Coverage in Medical Cases in the ICU at Dr. Cipto Mangunkusumo National General Hospital: A Cost Analysis Study - Meirina; Vera Irawany; Sidharta Kusuma Manggala (Jurnal Sehat Indonesia (JUSINDO), 2026)
In the prospective payment system based on INA-CBGs, understanding the relationship between patient clinical complexity and the proportion of intensive care unit (ICU) costs relative to the INA-CBGs tariff is essential for evaluating service efficiency and equity in health financing allocation. However, few empirical studies in Indonesia have examined how factors such as the mSOFA score, mechanical ventilation use, hemodialysis, and length of ICU stay relate to ICU cost proportions. This prospective cohort study was conducted at Dr. Cipto Mangunkusumo National General Hospital from 1 January to 31 March 2026, involving 46 adult patients admitted to the medical ICU with complete INA-CBGs claims. Data were extracted from electronic medical records and the hospital’s financial information system, including daily mSOFA scores, mechanical ventilation status, hemodialysis administration, ICU length of stay, actual ICU costs, and corresponding INA-CBGs tariffs. The analysis showed that no increase in ICU cost proportion was observed with higher mSOFA scores or longer ICU stays. In contrast, variability in cost proportion decreased among patients with mSOFA ≥6 and ICU stays longer than four days, suggesting that in critically ill patients with high disease severity, ICU costs become relatively more predictable compared with INA-CBGs tariffs. ICU cost proportion is not determined linearly by a single intervention but instead results from a complex interplay among disease severity, accuracy of diagnosis and procedure coding, and daily clinical dynamics during ICU admission.